Urban Green Spaces - Alexandre Castanho, Rui; Cabezas Fernández, José (IntechOpen, 2022)
Urban planning intends to promote urban living conditions through reasonable land use, always maintaining harmony between urban planning and nature. The cities are the focus of growth within states; their industrialization and growth in housing large populations worldwide have caused a disordered and chaotic development. The objective of planning is to correct the urban chaos and prevent it from happening again due to inadequate planning, thus improving inhabitants' quality of life. Contextually, urban green spaces are a pivotal piece of this puzzle. In fact, the existence of abundant vegetation in cities has a universal appeal that persists beyond temporal, spatial, and cultural divisions, incorporating itself within the concept of environmental quality and leading to a better quality of life. Thereby, it is essential to assess and analyze the design, function, and role of urban green spaces in today's and tomorrow's cities.